Moving towards company-community partnerships: elements to take into account for fast-wood plantation companies in Indonesia - Maturana, J.; Hosgood, N.; Suhartanto, A.A. (2005)
This study looks at two important fast-wood plantation issues in Indonesia, the impact of land claims and the role of partnership schemes. The study was conducted in collaboration with some of the nation’s largest plantation companies. Land claims have a significant impact on plantation companies and continue to affect a sizeable land area, despite the many years and costly efforts of companies to reduce the size and number of these claims. Partnership schemes have achieved very modest results, with many communities preferring not to participate in planting fast-wood trees. This document examines land claims using historical data. It also details the use by communities of a recently developed ‘participatory’ method to bring light to these issues. Although the data and analysis is focused on Indonesia, the conclusions may be applied to similar situations in other tropical countries and help improve the ways companies and communities co-exist and engage with each other.